SHARIA COMPLIANCE DAN KINERJA KEUANGAN PADA BANK SYARIAH DI INDONESIA - Debbi Chyntia Ovami (JURNAL MUTIARA AKUNTANSI, 2020)
The purpose of this study was to determine the effect of Sharia Compliance as proxied by the Islamic Income Ratio, Profit Sharing Ratio and Islamic Investment Ratio as a proxy for financial performance at Sharia Banks in Indonesia. The population was sharia banks registered in the Financial Service authority in the period of 2016-2018. The total sample used was 13 samples taken by using census sampling technique . The analytical method used in this study is multiple regression. The results of this study indicate that the Islamic Income Ratio, Profit Sharing Ratio and Islamic Investment Ratio as a proxy simultaneously influence the financial performance. Partially Islamic Income Ratio had positive and significant influence on financial performance, while the Profit Sharing Ratio and Islamic Investment Ratio had positive and insignificant influence on financial performance at Sharia Banks in Indonesia